Strategi Komunikasi Pemasaran Answear Stuff Melalui Media Sosial Instagram - David Ferdiansyah (Jurnal Ekonomi dan Bisnis Digital, 2024)
Having Internet Network acces makes it easier for people to carry out various activities such as doing bussines or selling. Answear stuff is a second-hand brand chloting store that uses Instagram social media as a tool to market its product. Marketing communication strategis carried out on Instagram are a way to make it easier to do bussines and sell via social media. This research is to determine the marketing communication strategy for answear stuff via Instagram social media. Meanwhile, the theory used is marketing communication theory with 7P Marketing mix. The method used in this research is a qualitative research method which will discus marketing answear stuff through social media Instagram, answear stuff utilizes Instagram in carrying out marketing communication strategies by utilizing the features available on instagram.